2004
DOI: 10.1021/ma0492317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steric Repulsion on Helical Conformation of Poly(N-propargylamides) with Phenyl Groups

Abstract: N-Propargylamides with one, two, and three phenyl groups at the R-position of the carboxyl group [HC≡CCH2NHCOR; 1, R ) C(CH3)2C6H5; 2, R ) CCH3(C6H5)2; 3, R ) C(C6H5)3] were polymerized with a rhodium catalyst, (nbd)Rh + B -(C6H5)4 (nbd ) 2,5-norbornadiene), to obtain the corresponding polymers in 85-91% yields. Poly(1) possessed a moderate molecular weight (Mn ) 6300) and was thoroughly soluble in chloroform and dichloromethane. On the other hand, poly(2) and poly(3) were not totally soluble in the solvents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 23 publications
2
88
1
Order By: Relevance
“…In the spectrum of M4, only one strong absorption peak could be observed at around 265 nm, originating in the thiourea and phenyl ring in the monomer [32]. In the spectrum of poly(4), besides the absorption peak around 265 nm, we can see a moderate absorption at about 310 nm, supporting the fact that poly(4) possess conjugated polyacetylene backbones [33]. The results with respect to UV-Vis absorption spectra are similar to some mono-substituted polyacetylenes studied by us earlier, e.g., poly(N -propargylsulfamide)s [34] and poly(N -propargylurea)s [26].…”
Section: Uv-vis Spectrum Of M4 and Poly(4)mentioning
confidence: 71%
“…In the spectrum of M4, only one strong absorption peak could be observed at around 265 nm, originating in the thiourea and phenyl ring in the monomer [32]. In the spectrum of poly(4), besides the absorption peak around 265 nm, we can see a moderate absorption at about 310 nm, supporting the fact that poly(4) possess conjugated polyacetylene backbones [33]. The results with respect to UV-Vis absorption spectra are similar to some mono-substituted polyacetylenes studied by us earlier, e.g., poly(N -propargylsulfamide)s [34] and poly(N -propargylurea)s [26].…”
Section: Uv-vis Spectrum Of M4 and Poly(4)mentioning
confidence: 71%
“…Rh catalysts can polymerize only monosubstituted acetylenes such as phenylacetylene and its ring-substituted derivatives, [6][7][8][9][10][11] N-propargylamides, [12][13][14][15][16][17] and propiolic esters. [19][20][21][22][23] The Rh-catalyzed polymerization proceeds by the insertion mechanism, and features excellent tolerance to polar subsituents in the monomer 24,25 and protic solvents.…”
mentioning
confidence: 99%
“…[24][25][26][27][28][29] However, the cis olefinic proton signal was not observed in the 1 H NMR spectrum of poly(M-PMMA), probably because of the low mobility of the polyacetylene main chain. 50 The GPC traces of M-PMMA and poly(M-PMMA) (Run 4, Table I) are illustrated in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] There are several classes of wellordered synthetic helical polymers including poly-(alkyl methacrylates), [6][7][8][9] polychloral, 10,11 polyisocyanides, [12][13][14][15] polyisocyanates, [16][17][18][19] and polysilanes. [20][21][22][23] Besides, some helical polyacetylenes have been synthesized by Rh-catalyzed polymerization of acetylenic monomers having chiral side groups such as chiral carboxylic acids, [24][25][26][27][28][29] alcohols, [30][31][32][33] amino acids, [34][35][36][37][38][39][40] sugars [41][42][43] and terpenes 44 as the helical sources. Recently, our laboratory reported that (S)-1-methylpropargyl alcohol served as a powerful helical source for substituted polyacetylenes.…”
mentioning
confidence: 99%